2015
DOI: 10.1136/bmjopen-2015-008244
|View full text |Cite
|
Sign up to set email alerts
|

Identifying low-value clinical practices in critical care medicine: protocol for a scoping review

Abstract: IntroductionReducing unnecessary, low-value clinical practice (ie, de-adoption) is key to improving value for money in healthcare, especially among patients admitted to intensive care units (ICUs) where resource consumption exceeds other medical and surgical populations. Research suggests that low-value clinical practices are common in medicine, however systematically and objectively identifying them is a widely cited barrier to de-adoption. We will conduct a scoping review to identify low-value clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Results from the two sets of searches established the target ‘cohort’ of articles that was subsequently analyzed within a framework to describe reproducibility of experimental clinical research (Table 1 ). Our methods are outlined in a detailed, published protocol [ 25 ] and depicted within Additional file 1 : Figure S1. The published protocol indicates intention to include systematic reviews, systematic reviews with meta-analyses, and studies examining the clinical effects of diagnostic interventions within the target cohort of articles; however, at the request of the reviewers, these studies were removed from this manuscript.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the two sets of searches established the target ‘cohort’ of articles that was subsequently analyzed within a framework to describe reproducibility of experimental clinical research (Table 1 ). Our methods are outlined in a detailed, published protocol [ 25 ] and depicted within Additional file 1 : Figure S1. The published protocol indicates intention to include systematic reviews, systematic reviews with meta-analyses, and studies examining the clinical effects of diagnostic interventions within the target cohort of articles; however, at the request of the reviewers, these studies were removed from this manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were excluded if (1) study participants were primarily admitted to coronary care units [ 28 ], (2) the clinical practice was provided exclusively in the pre-hospital setting, or (3) the study examined diagnostic accuracy or outcomes associated with the use of a diagnostic intervention. For the secondary searches, studies were retained if they fit the primary search eligibility criteria AND represented an ‘ original study’ OR a ‘ reproduction attempt ’ of a study identified in the primary search (Table 1 ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients admitted to the Intensive Care Unit (ICU) are the sickest individuals in the hospital (Niven et al 2015). They are often physiologically unstable and require complex, invasive treatment to manage their care.…”
Section: Introductionmentioning
confidence: 99%
“…Few have undertaken a systematic approach to identifying candidates for de-adoption, although this has recently been proposed by a group of Canadian critical care researchers. 12 A systematic review published in 2007 examined variables affecting physicians' test-ordering tendencies. 13 They found that modifiable variables that affected testordering behaviours included perceived or real medicolegal concerns, personal beliefs on the usefulness of certain tests, individual risk-taking attitudes of the physicians, and financial incentives.…”
Section: "Waste" In the Ed: What Is It And Why Does It Exist?mentioning
confidence: 99%